PEMANFAATAN LIMBAH KULIT KOPI: STRATEGI PENGOLAHAN CASCARA TEA UNTUK MENINGKATKAN NILAI EKONOMI LOKAL - Kencanawati, Indah; Saslina, Tri; Mairisiska, Titin; Anzalina, Hofifah (Institut Agama Islam Negeri Kerinci, 2023)
Public understanding regarding the processing of Cascara Tea has undergone significant changes, especially in knowledge regarding processing techniques which produce various variations of products that attract the attention of consumers. The research method applied is a descriptive analysis method, involving several stages which form the basis of the data collection and analysis process, including the use of primary data and secondary data. This stage includes research planning, subject selection, and data collection through in-depth interviews, participant observation, and document analysis. The data analysis process is carried out through techniques for organizing, translating, and interpreting data, which includes coding, categorization, and identifying patterns of findings. The research results show that the reconstruction of community activities in the production of Cascara Tea Kerinci involves several key aspects. Among other things, Cascara Tea Kerinci is known for its unique quality when compared to similar products, various product variations, and attention to the quality of Cascara Tea Kerinci products. In addition, there are ongoing efforts to create new variants from time to time to maintain consumer interest in this product. the unique characteristics of Cascara Tea Kerinci became one of the main factors in this reconstruction, creating a product identity that cannot be competed with on the market.